Progress of Middle Meningeal Arterial Embolization for Chronic Subdural Hematoma - Tang, Qingfan; Zhang, Yi; Liu, Lei (Journal of Contemporary Medical Practice, 2024)
Chronic subdural hematoma (intermediate intracranial hemorrhage, CSDH) is a space-occupying disease, which is mostly common in neurosurgery and more common in old age. At present, surgical treatment is mainly used, but the postoperative recurrence rate is high, which is the most important treatment method at present. As a new treatment for CSDH, meningeal artery embolization has been found to block the blood supply of CSDH, but there is no further research and recognized consensus. The authors summarized the progress of anatomical research, technical methods and precautions, material selection and therapeutic effect of meningeal arterial embolism for CSDH.